1994
DOI: 10.1002/bem.2250150202
|View full text |Cite
|
Sign up to set email alerts
|

Microwave irradiation affects radial‐arm maze performance in the rat

Abstract: After 45 min of exposure to pulsed 2450 MHz microwaves (2 microseconds pulses, 500 pps, 1 mW/cm2, average whole body SAR 0.6 W/kg), rats showed retarded learning while performing in the radial-arm maze to obtain food rewards, indicating a deficit in spatial "working memory" function. This behavioral deficit was reversed by pretreatment before exposure with the cholinergic agonist physostigmine or the opiate antagonist naltrexone, whereas pretreatment with the peripheral opiate antagonist naloxone methiodide sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
93
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(95 citation statements)
references
References 34 publications
1
93
1
Order By: Relevance
“…Activation of endogenous opioids by microwaves seemed to play an important mediating role in some of these effects. Recent results by Lai indicate an important role for the cholinergic system and endogenous opioids in the microwave-induced spatial memory deficit in the radial-arm maze (31). These results suggest that the effect of microwaves on working memory also involves the cholinergic system, also modulated by endogenous opioids, and moreover that only central, and not peripheral, endogenous opioids are responsible for the effect.…”
Section: Effects Of Amplitude-modulated Radiofrequency Radiation In Vivomentioning
confidence: 87%
See 1 more Smart Citation
“…Activation of endogenous opioids by microwaves seemed to play an important mediating role in some of these effects. Recent results by Lai indicate an important role for the cholinergic system and endogenous opioids in the microwave-induced spatial memory deficit in the radial-arm maze (31). These results suggest that the effect of microwaves on working memory also involves the cholinergic system, also modulated by endogenous opioids, and moreover that only central, and not peripheral, endogenous opioids are responsible for the effect.…”
Section: Effects Of Amplitude-modulated Radiofrequency Radiation In Vivomentioning
confidence: 87%
“…Carrier frequencies of 2.45 GHz or around 900 MHz (880-1000 MHz) have been used in most of the studies. Effects at relatively low SAR values have been repoi-ted at both frequencies, although there is a tendency towards the use of high SAR values or, if the timeaveraged SAR is low, very high peak SAR values in experiments conducted using the 2.45-GHz carrier frequency (31,43,44). In the only study at 9 GHz (19), a high time-averaged SAR of 90 Wlkg was used.…”
Section: Discussionmentioning
confidence: 99%
“…However, the calculated energy in the pulse (2.4 mJ/kg peak, peak SAR 2400 W/kg) would result in hearing auditory clicks [Chou et al, 1985b]. Lai et al [1994] and Wang and Lai [2000] may have statistical problems, since the exposed and sham animals exhibited no apparent interaction between testing days and treatment. Mickley et al [1994] found that acute exposure to 600 MHz fields at SARs up to 10 W/kg for 20 min produced deficits in working memory in rats when the temperature in brain and rectum was raised by 1 8C.…”
Section: Cognitive Studiesmentioning
confidence: 99%
“…There were no differences among exposed, sham, and cage control rats in the two spatial learning tasks. Cobb et al [2003] reexamined the possibility for changes in ''working'' memory in rats following whole body exposure to MWexposure [Lai et al, 1994]. For each of 10 days, they exposed rats within circular polarized waveguides for 45 min to 2450 MHz fields at whole body SARs of 0.6 W/kg, 2 ms pulses, 500 pps, followed by testing in a 12 arm radial maze.…”
Section: Cognitive Studiesmentioning
confidence: 99%
“…For instance, many studies have found that, at a 900MHz frequency band, radiations from mobile phones or telecommunication antennas have no effect on the memory or the brain function in animals (1-4) or humans (5,6). However, a number of studies have reported changes in brain function or memory dysfunction with 1 800 and 2 400 MHz frequency bands (7,8). Brain dysfunction can inadvertently increase anxiety in humans.…”
Section: Introductionmentioning
confidence: 99%